2017
DOI: 10.1073/pnas.1707522114
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cue-independent spatial representation in the human auditory cortex during active listening

Abstract: Few auditory functions are as important or as universal as the capacity for auditory spatial awareness (e.g., sound localization). That ability relies on sensitivity to acoustical cues-particularly interaural time and level differences (ITD and ILD)-that correlate with sound-source locations. Under nonspatial listening conditions, cortical sensitivity to ITD and ILD takes the form of broad contralaterally dominated response functions. It is unknown, however, whether that sensitivity reflects representations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 80 publications
5
28
0
Order By: Relevance
“…However, in the present Varying Frontal Distance condition, the stimuli contained both DRR and intensity-related distance cues, i.e., all possible available cues. Our previous behavioral studies suggest that in cases like this, auditory distance-discrimination performance is based on an integrated representation of source distance cues instead of any individual distance cue alone (level, ILD, or DRR) (Kopco et al, 2012), consistent with recent fMRI findings regarding horizontal direction cue processing (Higgins et al, 2017). The areas activated more strongly to frontal distance changes than intensity changes could thus involve both DRR specific populations and networks that assemble independent features to a more integrated spatial representation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in the present Varying Frontal Distance condition, the stimuli contained both DRR and intensity-related distance cues, i.e., all possible available cues. Our previous behavioral studies suggest that in cases like this, auditory distance-discrimination performance is based on an integrated representation of source distance cues instead of any individual distance cue alone (level, ILD, or DRR) (Kopco et al, 2012), consistent with recent fMRI findings regarding horizontal direction cue processing (Higgins et al, 2017). The areas activated more strongly to frontal distance changes than intensity changes could thus involve both DRR specific populations and networks that assemble independent features to a more integrated spatial representation.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, roughly the same areas showed overlapping activations to individually presented ILD and ITD cues in a recent fMRI study (Higgins et al, 2017). It is thus possible that the posterior AC areas that were activated by frontal distance cues include neuron populations that process representations of the auditory space instead of individual acoustic features only (Higgins et al, 2017;Palomäki et al, 2005), although these representations may not have an orderly topographical organization comparable to cortical representations of the visual space (Salminen et al, 2009;Stecker and Middlebrooks, 2003).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies argued that successful cross-condition classification reflects an abstract representation of stimuli conditions (Fairhall and Caramazza, 2013;Higgins et al, 2017;Hong et al, 2012).…”
Section: Mvpa -Across-conditionmentioning
confidence: 99%
“…Significant cross-condition classification has typically been considered as a demonstration that the region implements a partly common and abstracted representation of the tested conditions (Fairhall and Caramazza, 2013;Higgins et al, 2017;Hong et al, 2012). For instance, a recent study elegantly demonstrated that the human auditory cortex at least partly integrates interaural time and level differences (ITD and ILD) into a higher-order representation of auditory space based on significant for cross-cue classification (training on ITD and classifying ILD, and reversely).…”
Section: Does Hpt Contain Information About Specific Motion Directionmentioning
confidence: 99%